2008
DOI: 10.1007/s12195-008-0038-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Hydraulic Pressure and Fluid Flow Differentially Modulate Cytoskeleton Re-Organization in MC3T3 Osteoblasts

Abstract: Mechanical loads are essential towards maintaining bone mass and skeletal integrity. Such loads generate various stimuli at the cellular level, including cyclic hydraulic pressure (CHP) and fluid shear stress (FSS). To gain insight into the anabolic responses of osteoblasts to CHP and FSS, we subjected MC3T3-E1 preosteoblasts to either FSS (12 dynes/cm 2 ) or CHP varying from 0 to 68 kPa at 0.5 Hz. As with FSS, CHP produced a significant increase in ATP release over static controls within 5 min of onset. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 55 publications
(120 reference statements)
4
76
1
1
Order By: Relevance
“…12) In the meantime, F-actin begins to polymerize, gradually increasing the cell stiffness and the cellular mechanical threshold. 20,25) The combined effects of the 3-min sFSS stimulation and the following rest period reinforce F-actin stress fibers in 10 min of rest, but weaken F-actin stress fibers thereafter, and ultimately lead to the Several limitations exist in our study. First, we showed that F-actin regulated mechanosensitive channel(s) influenced mechanosensitivity recovery in MC3T3-E1 cells during a rest period.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…12) In the meantime, F-actin begins to polymerize, gradually increasing the cell stiffness and the cellular mechanical threshold. 20,25) The combined effects of the 3-min sFSS stimulation and the following rest period reinforce F-actin stress fibers in 10 min of rest, but weaken F-actin stress fibers thereafter, and ultimately lead to the Several limitations exist in our study. First, we showed that F-actin regulated mechanosensitive channel(s) influenced mechanosensitivity recovery in MC3T3-E1 cells during a rest period.…”
Section: Discussionmentioning
confidence: 89%
“…20,24) In bone tissue, cells are exposed to a variety of mechanical stimulations, such as FSS, hydrostatic pressure, and stretching. sFSS stimulation has been shown to increase the polymerization of actin monomers, 25) F-actin alignment, 26) and microtubule remolding, 25) which indicate adaptation of cells to external stimulation. However, this may also cause an increase in the cellular mechanical threshold, and thus, decrease the mechanosensitivity in continuously loaded cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study also demonstrated that cyclic hydraulic pressure and fluid flow differentially modulate cytoskeleton re-organization in MC3T3 osteoblasts. This was suggested to contribute to the loss of mechanosensitivity with extended loading [197].…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%
“…4) Previous studies on mouse chondrocytes have reported the use of hydrostatic pressures in the range 10-70 kPa applied at 0.25-1 Hz for short (5,15,30, and 60 min) or long periods (1 h daily for up to 19 days). 5,6) In this study, a similar range of pressure, 5-37 kPa at 0.5 Hz, was loaded 1 h daily for 3 days.…”
mentioning
confidence: 99%